Optimizing Oil Palm (Elais guinensis L.) Carbon Management in Tidal Lands to Support Sustainable Plantations - Ismail, Ismail; Wahyudin, Cecep; Haryono, Triyo (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Oil palm plantations in tidal areas face complex challenges in optimizing carbon management to achieve sustainable production. This study aims to analyze the dynamics of carbon stocks across various management systems of oil palm plantations in tidal zones and to develop optimization strategies for sustainable production. The research was conducted in Menten Village, Rambutan District, Musi Banyuasin Regency, South Sumatra, employing a factorial Randomized Complete Block Design with factors including water management systems (conventional, semi-intensive, conservation, optimization) and plant age categories (3–5, 6–10, 11–15, 16–20, and 21–25 years). CO₂ emissions and sequestration were measured using the LI-COR LI-8100A system; biomass was assessed through allometric equations and destructive sampling methods, while soil and water parameters were analyzed using standard procedures. The results demonstrated that the optimized system incorporating smart drainage achieved the best performance, exhibiting the lowest CO₂ emissions (6.2 Mg C/ha/year), the highest carbon absorption (21.5 Mg C/ha/year), and a positive net carbon balance (+15.3 Mg C/ha/year) with an efficiency of 346.8%. This system also increased fresh fruit bunch (FFB) productivity from 18.5 tons/ha/year under conventional management to 26.4 tons/ha/year, with superior quality metrics (oil content: 27.2%, acid value: 1.4%, crude palm oil yield: 25.2%). Total carbon stock progressively increased from 23.7 Mg C/ha in young plants to 147.9 Mg C/ha in mature plants, with an optimal sequestration rate of 17.8 Mg C/ha/year. The implementation of smart drainage, combined with IoT technology and biochar application, effectively optimized edaphic conditions by increasing soil pH to 4.8, raising organic carbon content to 4.2%, reducing bulk density to 0.68 g/cm³, and controlling salinity at 1.2 dS/m. This study confirms that oil palm plantations on tidal lands can achieve sustainability through precision agriculture practices that integrate precision water management, biochar application, and real-time monitoring to optimize the balance between productivity and carbon conservation.